Silyl radical-mediated activation of sulfamoyl chlorides enables direct access to aliphatic sulfonamides from alkenes - Hell, SM; Meyer, CF; Laudadio, G; Misale, A; Willis, MC; Noël, T; Trabanco, AA; Gouverneur, V (American Chemical Society, 2019)
Single electron reduction is more challenging for sulfamoyl chlorides than sulfonyl chlorides. However, sulfamoyl and sulfonyl chlorides can be easily activated by Cl-atom abstraction by a silyl radical with similar rates. This latter mode of activation was therefore selected to access aliphatic sulfonamides, applying a single-step hydrosulfamoylation using inexpensive olefins, tris(trimethylsilyl)silane, and photocatalyst Eosin Y. This late-stage functionalization protocol generates molecules as complex as sulfonamide-containing cyclobutyl-spirooxindoles for direct use in medicinal chemistry.